2012
DOI: 10.1021/bm300194b
|View full text |Cite
|
Sign up to set email alerts
|

Mussel-Inspired Immobilization of Vascular Endothelial Growth Factor (VEGF) for Enhanced Endothelialization of Vascular Grafts

Abstract: Most polymeric vascular prosthetic materials have low patency rate for replacement of small diameter vessels (<5 mm), mainly due to failure to generate healthy endothelium. In this study, we present polydopamine-mediated immobilization of growth factors on the surface of polymeric materials as a versatile tool to modify surface characteristics of vascular grafts potentially for accelerated endothelialization. Polydopamine was deposited on the surface of biocompatible poly(L-lactide-co-ε-caprolactone) (PLCL) el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
104
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(110 citation statements)
references
References 38 publications
(65 reference statements)
4
104
0
Order By: Relevance
“…They are serious problems especially for small diameter artificial vascular grafts. [22][23][24][25][26] To improve graft patency, thrombus formation and neointimal hyperplasia should be controlled. Early stage endothelialisation offers a potential solution.…”
Section: Discussionmentioning
confidence: 99%
“…They are serious problems especially for small diameter artificial vascular grafts. [22][23][24][25][26] To improve graft patency, thrombus formation and neointimal hyperplasia should be controlled. Early stage endothelialisation offers a potential solution.…”
Section: Discussionmentioning
confidence: 99%
“…As a simple, versatile, and effective strategy to promote cell adhesion onto substrates with various material type and shape under solvent-free and non-toxic condition, polydopamine (PDA) films has attracted much attention in the field of biomaterials surface modification since Lee et al reported it in 2007 [41] . In the field of vascular biomaterials, PDA coating has been used as an immobilization layer for vascular endothelial growth factor (VEGF) [42,43] , heparin [44,45] , etc., and has also been used to control cell behaviors directly on the surface, which demonstrated that human umbilical vein endothelial cells (HUVECs) could adhere well and spread with a high viability on PDA coating [46][47][48] ; moreover, it showed that PDA coating on 316L stainless steel stent decreased adhesion and proliferation [48] .…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…63 VEGF was also immobilized through a simple dipping methodology after PDA was deposited on the surface of a poly(l-lactide-co-e-caprolactone) (PLCL) film. 84 VEGFdopamine coatings demonstrated accelerated HUVEC migration and proliferation compared to dopamine-coated or uncoated PLCL films. The group also was able to immobilize basic fibroblast growth factor, demonstrating the versatility of the PDA immobilization techniques.…”
mentioning
confidence: 91%